In Situ Printing and Functionalization of Hybrid Polymer-Ceramic Composites Using a Commercial 3D Printer and Dielectrophoresis—A Novel Conceptual Design - Georgios Tselikos (MDPI AG, 2021)
Three-dimensional printing-based additive manufacturing has emerged as a new frontier in materials science, with applications in the production of functionalized polymeric-based hybrid composites for various applications. In this work, a novel conceptual design was conceived in which an AC electric field was integrated into a commercial 3D printer (-based fused filament fabrication (FFF) working principle) to in situ manufacture hybrid composites having aligned ceramic filler particles. For this work, the thermoplastic poly lactic acid (PLA) was used as a polymer matrix while 10 vol% KNLN (K0.485Na0.485Li0.03NbO3) ceramic particles were chosen as a filler material. The degree of alignment of the ceramic powders depended upon print speed, printing temperature and distance between electrodes. At 210 °C and a 1 kV/mm applied electric field, printed samples showed nearly complete alignment of ceramic particles in the PLA matrix. This research shows that incorporating electric field sources into 3D printing processes would result in in situ ceramic particle alignment while preserving the other benefits of 3D printing.